Chapter 1: Kura koorliny – Introduction: What is the project? - Buchanan, J.; Collard, Len; Cumming, Ingrid; Palmer, David; Scott, Kim; Hartley, John (Cultural Science, 2016)
In 2006 Justice Murray Wilcox of the Federal Court of Australia found that native title continued to exist in Noongar3 boodjar (country). The decision demonstrated one of the world’s most remarkable examples of cultural and physical resilience on the part of an Indigenous group. This is particularly so when one understands the onerous demands placed on claimant groups, to provide (i) detailed evidence of a distinct culture and set of practices at the time of ‘sovereignty’, (ii) the claim-group’s continuity of language and knowledge, and (iii) demonstrated knowledge of and connection to ancestors at the time of ‘sovereignty’. Kingsley Palmer, author of the Single Noongar Claim’s Expert Anthropologist Report, concluded that the maintenance of Noongar knowledge, language and culture is monumental ‘testimony to an enduring Indigenous tradition that continues to survive despite the odds’. The following Report includes stories of present-day efforts to maintain this tradition of cultural resilience through novel, contemporary and globally networked means. It includes stories about a project that took as its dual aims (i) to carry out research concerned with bringing together old Noongar knowledge and new social media, and (ii) to make the social effort to build a digital platform that helps to make information about Noongar culture and ancient traditions available to the public, as well as to Noongar ‘users’ of that language and culture. In this way it is a story about research being used to support attempts at social and cultural development: research as social enterprise, and as ‘creative citizenship’.